Effects of creatine supplementation on oxidative stress profile of athletes - Percario, S.; Domingues, S. P.; Teixeira, L. F.; Vieira, J. L.; de Vasconcelos, F.; Marques Ciarrocchi, D.; Dias Almeida, E.; Conte, M. (Journal of the International Society of Sports Nutrition, 2012)
Creatine (Cr) supplementation has been widely used among athletes and physically active individuals. Secondary to its performance-enhancing ability, an increase in oxidative stress may occur, thus prompting concern about its use. The purpose of this study is to investigate the effects of Cr monohydrate supplementation and resistance training on muscle strength and oxidative stress profile in healthy athletes.